Analyzing the Students’ Needs for Cross-Interest English Program of 2013 Curriculum in Indonesia - Nurhidayati Putri (Postgraduate School, Universitas Negeri Padang, 2019)
ABSTRACT Cross-interest is a curricular program that is prepared to expand the students’ choice of interest, talent, and/or academic skill aside from the interest-based program (Permendikbud No.64/2014). Based on the researcher’s preliminary observation to some students and teachers, it was inferred that the application of the English Cross-Interest in SMAN 3 Bukitinggi had been good. However, there were some problems found. They were assumed as the effect of inexistence or lacks of needs analysis. Thus, the aim of this research was to investigate the target and learning needs of the students in the program. To fulfill such an aim, three instruments were used to collect the data; the researcher itself as the instrument, questionnaire, and interview guide. Descriptive research was applied as the research method where the grade XI students of SMAN 3 Bukittinggi were chosen as respondents of the research. Then, the result showed that the students’ target needs are mainly related to their academic and occupational English in the future. The students have been proved to be lack in some micro-skills of speaking which will be needed in the target situations. But, speaking is not practiced much during their study in the program. Reading, on the other hand, is also considered as one of the main skills needed but luckily they have got sufficient reading skills in the program. It has also been concealed that the students need more various learning strategies from the teachers.